Felony Jury Sentencing in Practice: A Three-State study - King, Nancy J. (2004)
The Court's recent decision in Apprendi v. New Jersey, 530 U.S. 466 (2000), has prompted renewed interest in sentencing by jury in non-capital cases. Yet jury sentencing in felony cases remains one of the least understood procedures in contemporary American criminal justice. This Article looks beyond idealized visions of jury sentencing to examine for the first time how felony jury sentencing actually operates in three different states-Kentucky, Virginia, and Arkansas. Dozens of interviews with prosecutors, defenders, and judges, as well as an analysis of state sentencing data, reveal that this neglected corner of state criminal justice provides a unique window through which one can observe some of the most fundamental forces operating in criminal adjudication today. It turns out that jury sentencing in practice looks very little like jury sentencing in theory. Sentencing by jury is promoted for its democratic contribution, but its vitality may turn instead upon its ability to streamline case disposition and protect elected officials from political accountability for sentencing policy. Jury sentencing is viewed by these criminal justice insiders as a critical component of the justice system in each state, a tool they have adapted to deter trials, to accommodate elected judges, and to appease constituents who support ever higher sentences for crime. The Article explores the implications of this research for sentencing reform, and criminal justice reform generall